Attenuation of Morphine Withdrawal Syndrome by Various Dosages of Curcumin in Comparison with Clonidine in Mouse: Possible Mechanism - Motaghinejad, Majid (Iran J Med Sci, 2015)
BACKGROUND: Herbal medical compounds and their major constituent have been used in the management and treatment of opioid withdrawal syndrome and pain. This study was carried out to clarify the effect of curcumin, the major compound of turmeric, on morphine withdrawal syndrome in mouse model and its possible mechanisms of pain relieving activity by assessing in writhing test as a model of visceral pain. METHODS: Due to two separate protocols (withdrawal syndrome and pain), 144 male albino mice were divided in two major groups. In withdrawal syndrome group, test effect of various dosages of curcumin (10, 20, and 40 mg/kg) was assessed on withdrawal signs and compared with positive and negative control and standard treatment (clonidine 0.4 mg/kg) groups. In pain groups, to determine the mechanism of pain relieving activity of curcumin, various dosages of curcumin (10, 20, and 40 mg/kg) in three separated groups, were used against acetic acid induced writhing (which is a constriction) test. The most effective dose (40 mg/kg) was used in writhing test and compared with groups pretreated with antagonist of major neurotransmitters involved in pain; and compared with group pretreated with vehicle (DMSO, 0.05%) as control. RESULTS: Curcumin attenuates withdrawal syndrome in a dose dependent manner in comparison with the dependent positive control group (P<0.05). It also indicated that pretreatment with naloxone and cyproheptadine significantly attenuate antinociception effect of curcumin (P<0.05). CONCLUSION: This study advocate that antinociception of curcumin was mediated by opioidergic and adrenergic system.